Guess how much I love you - McBratney, Sam (Walker London, 2018)
"Sometimes, when you love someone very, very much, you want to find a way of describing how great your feelings are. But, as Little Nutbrown Hare and Big Nutbrown Hare discover, love is not an easy thing to measure!"--Book jacket